2013
DOI: 10.3109/01676830.2012.736595
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Histopathology of Lacrimal Gland Lesions in a Tertiary Referral Centre

Abstract: Chronic dacryoadenitis and lymphoproliferative disorders are the two commonest causes of lacrimal gland lesions in our series. Although many cases remain non-specific, about 60% have a specific inflammation that may be associated with a systemic disease. As one third of our patients with lymphoproliferative disease of the lacrimal gland had an associated systemic lymphoma, patients with such lesions should be referred for investigation of possible systemic lymphoma. The results of our study can aid in providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10] Bonavolontà et al 3 observed that dermoid cyst (14%) was the most common orbital disease noted in their study. On the other hand, Shields et al 6 and Jamison et al 10 reported idiopathic orbital inflammation and lymphoproliferative tumour as the two most common orbital diseases.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10] Bonavolontà et al 3 observed that dermoid cyst (14%) was the most common orbital disease noted in their study. On the other hand, Shields et al 6 and Jamison et al 10 reported idiopathic orbital inflammation and lymphoproliferative tumour as the two most common orbital diseases.…”
Section: Discussionmentioning
confidence: 75%
“…1,2 The heterogeneity of orbital diseases frequently poses a diagnostic dilemma to the attending clinicians. [3][4][5][6][7][8][9] When diagnosis cannot be made confidently on the ground of clinical and radiological findings, orbital biopsy is required to help achieve the definitive diagnosis before an appropriate management plan is formulated.…”
Section: Introductionmentioning
confidence: 99%
“…This study is the largest audit of lacrimal gland pathology ever and the first audit of lacrimal gland pathology in Australia. Similar audits have been conducted in Denmark (1974–2007, 232 cases), North America (1962–1987, 142 cases) and Singapore (2000–2010, 69 cases) . An audit of orbital biopsies has been undertaken in North America, and an audit of orbital tumours has been undertaken in Japan .…”
Section: Discussionmentioning
confidence: 90%
“…Secondly, the ratio of inflammatory biopsies to neoplastic biopsies will be significantly influenced, even within a tertiary centre, by each clincian's threshold for biopsying patients with presumed dacryoadenitis. Excluding LH, other reviews of lacrimal gland biopsy have found inflammations in 26.7%, 46% and 63.4% of lacrimal gland biopsies. Of the patients with biopsy‐confirmed dacryoadenitis in this series, biopsy (supported by adjunctive clinical investigations) revealed a specific aetiology in a significant proportion (34%) of cases.…”
Section: Discussionmentioning
confidence: 96%
“…Lacrimal gland tumors represent 5% to 35% of all orbital tumors. 11 Even though most of the lesions are inflammatory, a small proportion of them are malignant neoplasms and may be life-threatening. Diagnosis of lacrimal gland pathology is not accurate based on clinical presentation solely; therefore, a tissue biopsy is often necessary.…”
Section: Discussionmentioning
confidence: 99%